Tax-Response Heterogeneity and the Effects of Double Taxation Treaties on the Location Choices of Multinational Firms - Simon Behrendt; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines location choices of multinational enterprises (MNEs). We particularly focus on the consequences of double taxation treaties (DTTs) and corporate profit taxes on the probability to choose a location. DTTs have become a key policy instrument used by countries to regulate international tax issues related to the cross-border activities of MNEs. Based on three alternative location choice models, which all allow parameter estimates to vary randomly across firms, we show that firm responses to policy variables are highly heterogeneous. Postestimation statistics suggest that the heterogeneity of parameters is strongly correlated with firm size and effective tax burden, which is consistent with tax-avoidance behavior and provides an explanation for why tax-responses are heterogeneous in the first place. We quantify the (positive) effect of DTTs and demonstrate that the negative tax-responsiveness becomes larger if a DTT is implemented. The latter is evidence that provisions intended to prevent tax avoidance are effective.
Keywords: F23; H25; H26; 330; location choice; multinational firm; double taxation treaties; corporate income taxes